Theming and Imagineering as a Placemaking Strategy – A Case Study of Islamic Tourism in Malaysia - Khalid, Nurul Shakila; Muzaini, Hamzah (Universiti Sains Malaysia, 2016)
Malaysia has deployed many tourism themes, beginning with “Malaysia, Truly Asia” to the more temporal-specific themes of “Visit Malaysia Year” and “MyFest 2015” to portray its uniqueness within the context of the multiracial country. Malaysia aims to capitalise on the diversity of its attractions and transform them, via spatial imagineering, into fodder to materialise its marketing image as a Muslim country. Using the key concept of thematisation and imagineering, this study provides an understanding not only on how people shape places materially, socially and symbolically, but also the ways in which this has been contested. Drawing on in-depth interviews with local Malaysians from different ethnics background as the indirect stakeholders, the findings offer the constructivist and post-structuralism perspectives on seeing how Islamic tourism has been received in terms of making the country unique in order to enhance ethnic harmony, as much as to capture tourist imagination and capital investments to create new country imaginaries. Hence, to achieve the objectives of engineering of societies as meant to encourage locals to rediscover local places and attractions, and bridge understanding between multi-ethnicity populations towards the nationbuilding.